Analisis kesesuaian mutu air pada muara kanal Panampu Kota Makassar - Leonard, Franita; Hasanuddin, Hasanuddin (Teknosains: Media Informasi Sains dan Teknologi, 2023)
Abstract : Clean water which is increasingly scarce, with unsafe quality can affect the lives of living things around it so that it can cause new problems. This study aims to prevent a decrease in water quality in the estuary area of the Panampu Canal. This study used a descriptive exploratory research conducted by observing the location and analyzing the results of air quality measurements. The results of seawater quality testing on pH parameters obtained results of 7.1, BOD5 of 1.20 mg/L, DO of 6.30 mg/L, and Coliform Total of 50 MPN/100ml indicating that seawater quality is safe for the environment because it does not exceed quality standards that have been stipulated in the Government Regulation of the Republic of Indonesia No. 22 years of 2021. However, the temperature parameter with a value of 32.3 oC exceeds the set of quality standard. Based on these data, it is necessary to manage water quality because of parameters that exceed quality standards. Keywords: clean water, water quality; canal estuary.